USING COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) MODEL TO IMPROVE STUDENTS' WRITING SKILLS - Abdyta Elfrida Situmorang, - (2021)
This research aimed to investigate the use of Cooperative Integrated Reading and Composition (CIRC) in teaching writing the narrative text for senior high school students. This research was conducted under a classroom action research design which involved the researcher observing the phenomenon that occurred in the classroom and giving particular intervention, an English teacher and a collaborator. The participants of this study were 15 students from a Senior High School in Bintan, Indonesia. The data were obtained by assessing the students' writing skills through writing tests and by observing the teaching and learning process through the observation, field notes, and interview. The result indicated that the use of CIRC were likely to improve students' writing skills both individually or in groups. They were able to read and understand the text, utilize some related vocabulary, make the schema from their reading activity, and compose the schema becomes a simple story based on the text given by the teacher. In addition, the students were able to build the schema not only from reading the written text but also through reading multimodal text in picture series. At the end of the teaching and learning process, the students could write a complete story well. The students' writing became more advance in terms of the content or ideas of the story, organization, grammar, vocabulary, and mechanics since this model could accommodate the students' needs in learning writing through some activities. The implementation of various activities in the CIRC model would likely to successfully encourage students' enthusiasm in writing and made the students understand and respond to the researcher's instructions and explanations.